Implementasi Kebijakan Zonasi Tingkat SD, SMP di Kelurahan Kapas Madya Baru, Kecamatan Tambaksari, Surabaya - Fawaid; Muhammad Roisul Basyar (Policy and Maritime Review, 2023)
The zoning system is part of school reform in improving the quality of education in Indonesia. One of the government's efforts in examining education is issuing new policies for the acceptance of new students through Minister of Education and Culture Regulation No. 44 of 2019 concerning Acceptance of New Students in Kindergartens, Primary Schools, Junior High Schools, High Schools, Vocational High Schools. The purpose of this study is to describe the Implementation of New Student Admission Zoning Policy as an Effort to Check the Quality of Education at the State Primary Schools and  Junior High School Level in Kapas Madya Baru, Tambak Sari District Surabaya City. The author uses qualitative considerations with the literature study method. The focus of the study uses 6 variables according to Van Meter and Van Horn in Subarsono (2013: 99), namely the size and objectives of the policy, resources, characteristics of implementing agents, propensity/tendencies of  implementers, communication between organizations and activities, and economic environment, social and political .Technical data uses  technical data. The results of this study indicate that the Implementation of New Student Admission Zoning Policy as an Effort to Study Quality in Education (Study of Primary Schools and Junior High Schools Level in Kapas Madya Baru, Tambak Sari District Surabaya City) has held policies that are in line with the expected policies. Although it requires zoning policies, there are still some challenges. There are still obstacles to the implementation of the resource variable and the social, political and economic environment.